DESCRIPTIVE STUDY ON THE TEACHING WRITING TO THE FIRST YEAR STUDENTS OF SMPN 2 NAWANGAN PACITAN IN 2010/2011 ACADEMIC YEAR - KUMALASARI, HANIT NUGRAINI (2011)
This research aims at describing the teaching learning process of writing to the first year students of SMP N 2 Nawangan and to describe the problems faced by the teacher in process of teaching learning writing to the first year students of SMP N 2 Nawangan. In this research the data are derived from event, information and document. There are three techniques in collecting the data namely: interview, observation, and documentation. The data achieved from information related to the teaching learning process of writing, in form of the field note, interview scripts and document. The results of the research show that are: 1.Process of teaching learning writing to the first year students of SMP N 2 Nawangan, includes: a. objective of teaching writing. b. the curriculum. c. the syllabus. d. approach of teaching writing adopted by the teacher. e. material for teaching writing. f. the process of teaching writing. 2. The problems faced by the teacher during teaching writing, includes: class management, limited time, different capability of the students and unstable motivation of the students.